Hyperrealisme sculptuur = Hyperrealism sculpture - Ansenk, Emily 1970-; Letze, Otto 1954-; Perrell, Franklin Hill; Jooren, Marieke (Waanders Uitgevers, 2018)
With 'Hyperrealism: Sculpture' the Kunsthal Rotterdam, after the success of 'Hyperrealism'. 50 years of painting 'in 2017, the step to the third dimension. There is a unique selection of spatial works by important hyper-realistic sculptors from the past 50 years. From the early American pioneers including George Segal, Duane Hanson and John DeAndrea to the rise of the international movement, represented by Juan Muñoz (Spain), Maurizio Cattelan (Italy), Berlinde de Bruyckere (Belgium), and Ron Mueck, Sam Jinks and Patricia Piccinini (from Australia). Since the 1960s and 1970s, artists with techniques such as modeling, casting and painting have developed different approaches to a contemporary form of figurative realism. On the basis of various subjects, such as 'human replicas' and 'distorted reality', it is shown that the way we look at our bodies is constantly changing. The relationship with various trends in art history and the technical development of the early years of hyper-realistic sculpture to the current digital era is also discussed. Exhibition: Kunsthal Rotterdam, The Netherlands (10.03. - 01.07.2018)
Deze uitgave verschijnt ter gelegenheid van de tentoonstelling "Hyperrealisme sculptuur" in de Kunsthal Rotterdam van 10 maart tot en met 1 juli 2018
Keywords: Geschichte 1970-2016; Mensch -- Motiv; Fotorealismus; Plastik; Sculpture, Modern / Exhibitions / 20th century; Sculpture, Modern / Exhibitions / 21st century; Ausstellungskatalog -- Kunsthal Rotterdam -- 10.03.2018-01.07.2018 -- Rotterdam; Bildband